Identifying Heirs’ Property: Extent and Value Across the South and Appalachia - Thomson, Ryan; Bailey, Conner (Journal of rural social sciences, 2023)
A database of property tax records was used to locate and quantify the extent of heirs’ property across 11 states (Alabama, Florida, Georgia, Kentucky, Louisiana, Mississippi, North Carolina, South Carolina, Tennessee, Virginia, and West Virginia). Based on previously published work, an index of four variables was then developed to estimate the likelihood that a given parcel was heirs’ property. The authors conservatively estimate that there are at least 496,994 parcels of heirs’ properties with a combined total area of 5.3 million acres and a market value of $41.9 billion in these states.